Pharmacy Malpractice Prevention: Strategies and Legal Perspectives - Coffman, Jonathan A.; Murray, Peter E.; Garcia-Godoy, Franklin (Advances in Social Sciences Research Journal, 2025)
Pharmacy malpractice poses serious risks to patient safety and exposes healthcare providers to significant legal liability. This study examines the critical strategies for preventing pharmacy malpractice through a comprehensive analysis of preventative strategies, legal frameworks, and best practices. It represents the first investigation into the proportion of legal malpractice cases to identify the most common pharmacy errors and their underlying causes. The study utilized the Google Scholar case law database to identify pharmacy malpractice cases. The search terms included patient age, health status, pharmacy type, healthcare specialty, malpractice types, and the nature of legal claims. The analysis focused on identifying patterns in malpractice allegations and the most frequently implicated healthcare providers and settings. The results revealed that the majority of malpractice allegations occurred during the care, treatment, and diagnosis stages, with most incidents taking place in pharmacies, hospitals, and clinics. Physicians, administrators, and nurses were the most frequently named as defendants in pharmacy malpractice claims. A significant portion of malpractice claims stemmed from a pharmacist’s refusal or inability to fill medications. The healthcare specialties most linked to pharmacy malpractice included physical medicine and rehabilitation, internal medicine, pain management, surgery, and emergency medicine. The most prevalent legal claims against pharmacists were for malpractice, negligence, and breach of contract, the average legal settlement amounts for a general pharmacy clinic was between $132,185 to $274,887, and the average legal settlement for a compounding pharmacy was $438,221. These cases often involved misfilled prescriptions, incorrect dosages, adverse drug interactions, and inadequate patient counseling. In conclusion, pharmacy malpractice is unacceptable and preventable. Improving patient safety requires greater attention to accuracy, competence, and diligence in medication management. Strengthening pharmacist training, enhancing oversight, and implementing more robust safety protocols are essential steps toward reducing malpractice incidents and protecting patient health.